Integrating Ethical and Moral Values to Foster Patriotism and Build Student Character - Retno Sari, Lisa; Yuni Saputri, Rima; Permata Sari, Dian; Endi Fernanda, Fitra; Nurul Insani, Nisrina (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Jurai Siwo Lampung, 2026)
This study aims to analyze the integration of ethical and moral values in fostering students' sense of patriotism as an effort to build student character. This research employed a quantitative descriptive approach using a survey method. The research subjects consisted of 33 students of SMP Negeri 34 Bandar Lampung who were members of the student council (OSIS) and school task force. Data were collected through questionnaires distributed after the implementation of a socialization activity on strengthening ethical and moral values integrated with the value of patriotism. The collected data were analyzed using descriptive percentage analysis techniques. The results showed that the socialization activity received very positive responses from students with an average percentage of 87.41%, which falls into the very good category. The indicator analysis revealed that students' understanding of ethical values reached 88%, moral values 89%, students' social attitudes 86%, and patriotism attitudes 87%. These findings indicate that the integration of ethical and moral values through character education socialization activities can be an effective strategy in fostering students' sense of patriotism and developing character based on national values. Therefore, the cultivation of ethical, moral, and patriotic values needs to be continuously implemented through various educational activities in schools.